PENGUATAN KARAKTER KESOPANAN MELALUI MODEL PEMBELAJARAN PROJECT CITIZEN DALAM MATA PELAJARAN PENDIDIKAN PANCASILA DI KELAS XI SMA NEGERI 21 MEDAN TA. 2025/2026 - Aulya, Fahrysyah; Laila Siregar, Hapni; Siagian, Liber; Yunita, Sri; Habeahan, Sampitmo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the strengthening of politeness as part of civic disposition through the project citizen learning model in Pancasila Education subject of class XI SMA Negeri 21 Medan. The background of this study focuses on the low politeness character of students due to conventional learning methods. The purpose of this study is to determine the politeness character of students through the project citizen learning model in class XI SMA Negeri 21 Medan. The type of research used is descriptive research with qualitative research methods, this study collected data through observation, interviews with teachers and students, and documentation. The subjects studied were teachers and students of class XI-2. Data collection techniques used primary data and secondary data. Primary data was obtained through interviews, observation and documentation. Secondary data was obtained through books, journals, articles relevant to the research topic studied. Data analysis used in three stages: data reduction, data presentation and drawing conclusions. The results of this study indicate that the use of the Project Citizen learning model can improve students' politeness character through learning activities that require collaboration, discussion, and team problem solving. This character improvement is seen from the increase in mutual respect, the use of polite language, the ability to respect the opinions of others, responsibility, and cooperation among students. In addition, the research results show that strengthening the character of politeness is in accordance with Thomas Lickona's theory which emphasizes three aspects, namely moral knowing, moral feeling, and moral action.